The Historical Evolution of Violence in Competitive Sport: From Ancient Athletics to Modern Sport - Cuixia Li; Xuesong Bo, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This paper investigates the historical evolution of violence in competitive sports by examining its development and transformation over time. It begins with an exploration of the origins of violence in ancient sporting events, analysing the cultural and societal factors that contributed to its prevalence. The study then traces the gradual shift towards more regulated and controlled sports during the medieval and Renaissance periods, culminating in the establishment of modern sports in the 19th and 20th centuries. Additionally, it discusses the impact of this evolution on athletes' physical and mental well-being, as well as the ethical considerations related to the promotion of aggressive behaviour in sports. Through a comprehensive analysis of the historical development of violence in competitive sports, this paper illuminates the changing attitudes towards sportsmanship and fair play throughout history.